2015
DOI: 10.1111/dom.12446
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term administration of the glucagon receptor antagonist LY2409021 lowers blood glucose in healthy people and in those with type 2 diabetes

Abstract: Blockade of glucagon signalling in patients with type 2 diabetes is well tolerated and results in substantial reduction of fasting and postprandial glucose with minimal hypoglycaemia, but with reversible increases in aminotransferases. Inhibition of glucagon signalling by LY2409021 is a promising potential treatment for patients with type 2 diabetes and should be evaluated in longer clinical trials to better evaluate benefits and risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 26 publications
6
93
0
Order By: Relevance
“…In contrast, Wang et al [21] recently showed that weekly administration of a monoclonal glucagon receptor-targeting antibody caused normalisation of blood glucose in severely diabetic mice. Perhaps chronic blockade of the glucagon receptor elicits changes in the pancreas similar to GCGRdeletion or antagonist administration [16]. In the present study, all of the three methods were supposed to cause immediate and near complete glucagon deficiency.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…In contrast, Wang et al [21] recently showed that weekly administration of a monoclonal glucagon receptor-targeting antibody caused normalisation of blood glucose in severely diabetic mice. Perhaps chronic blockade of the glucagon receptor elicits changes in the pancreas similar to GCGRdeletion or antagonist administration [16]. In the present study, all of the three methods were supposed to cause immediate and near complete glucagon deficiency.…”
Section: Discussionmentioning
confidence: 50%
“…These results further support the notion that presence or absence of glucagon did not matter for the hepatic glucose production during insulinopenia. This is in contrast to insulin-independent diabetes, where both glucagon antagonism and immunoneutralisation lowers blood glucose [8,16,17].…”
Section: Discussionmentioning
confidence: 91%
“…The positive results of these preclinical studies have begun to translate into clinical impact, with impressive glucose lowering with small molecule glucagon receptor antagonists in diabetic individuals [4,50]. This demonstrates the contribution increased glucagon signalling makes to the diabetic state and the potential for large effects on glycaemia with antagonism.…”
Section: Glucagon Antagonismmentioning
confidence: 93%
“…Following decades during which reduced insulin action was viewed as the exclusive cause of diabetes mellitus and hormonal replacement proved transformative to diabetic individuals worldwide, renewed interest in glucagon has resulted in a rediscovered appreciation of the role this hormone plays in the pathophysiology of impaired glucose homeostasis [1][2][3]. This recent excitement for glucagon antagonism as a viable therapeutic approach stems from the tantalising preclinical results suggesting that reducing glucagon action or secretion will exert potent reductions in the elevated hepatic glucose production present in both type 1 and 2 diabetes mellitus [4][5][6][7][8]. Glucagon is secreted by the pancreatic alpha cell in response to changes in the local concentration of glucose, amino acids or insulin.…”
Section: Glucagon: Hormonal Mediator Of Hepatic Metabolismmentioning
confidence: 99%
“…58 Early clinical trials in patients with type 2 diabetes mellitus show promise. 59,60 Therefore therapies that modulate glucagon receptor signalling could potentially be used to treat the hyperglycaemia of type 1 diabetes mellitus. Potential limitations to this approach are early findings from studies in rodents that glucagon receptor modulation is associated with islet hyperplasia and disturbance in lipid metabolism in rodent studies, 61 clearly issues that need further investigation.…”
Section: Novel Drugs That Target the Glucagon Pathway And Alpha Cell mentioning
confidence: 99%